Burden of uterine fibroids in Italy: epidemiology, treatment outcomes, and consumption of health care resources in more than 5,000 women - Chiumente M; De Rosa M; Messori A; Proli EM (Dove Medical Press, 2017)
Marco Chiumente,1 Mauro De Rosa,2 Andrea Messori,2 Enrica Maria Proli3 1Scientific Direction, SIFaCT – Italian Society for Clinical Pharmacy and Therapeutics, Milan, 2Board of directors, SIFaCT - Italian Society for Clinical Pharmacy and Therapeutics, Milan, 3Hospital Pharmacy, Policlinico Umberto I, Rome, Italy Background and purpose: Epidemiological studies on uterine fibroids (UFs) are mostly based on surveys or analyses of small samples of patients. In 50% of women, the quality of life is worsened by disease-related symptoms; furthermore, treatments imply a remarkable health care cost. The aim of this observational study was to analyze a large sample of Italian patients with UFs and to assess the epidemiology, the appropriateness of treatments, and the consumption of disease-related resources. Methods: Data were collected through a data-linkage technique from five administrative databases. Women aged between 18 and 55 years and resident in three local health authorities (north–central–south Italy) were selected over the period from 1st January 2009 to 31st December 2015. The inclusion criteria were a surgical procedure with diagnosis of UFs or a pharmacological treatment with gonadotropin-releasing hormone (GnRH) analogs or ulipristal acetate. Besides the overall descriptive analysis, two comparisons were evaluated: surgery versus no surgery and treatment with GnRH analogs versus ulipristal acetate. Results: A total of 5,665 women with UFs were selected from an overall population of 2,400,000 people. In the north, 73.6% of patients underwent surgery, as opposed to only 16.7% in the south; 70% of surgeries were hysterectomies. The average cost per patient was €3,249 (duration of follow-up = up to 7 years). The southern district had the highest number of drug prescriptions; in particular, 49% of patients took >10 packages of GnRH analogs. Conclusion: This study is the first on this topic conducted in Italy using a large sample size. The analysis of resource consumption revealed a high heterogeneity in the choice of drug treatments by gynecologists (especially in the south); in the north, marked variations were seen in the rates of surgery. The long-term use of GnRH was inappropriate. Keywords: observational study, leiomyoma, ulipristal acetate, gonadotropin-releasing hormone, costs and cost analysis